An Actigraphy-Based Validation Study of the Sleep Disorder Inventory in the Nursing Home - Hjetland, Gunnhild J.; Nordhus, Inger Hilde; Pallesen, Ståle; Cummings, Jeffrey; Tractenberg, Rochelle E.; Thun, Eirunn; Kolberg, Eirin; Flo, Elisabeth (Frontiers in Psychiatry, 2020)
Background: Disrupted sleep is common among nursing home patients with dementia and is associated with increased agitation, depression, and cognitive impairment. Detecting and treating sleep problems in this population are therefore of great importance, albeit challenging. Systematic observation and objective recordings of sleep are time-consuming and resource intensive, and self-report is often unreliable. Commonly used proxy-rated scales contain few sleep items, which affects the reliability of the raters’ reports. The present study aimed to adapt the proxy-rated Sleep Disorder Inventory (SDI) to a nursing home context and validate it against actigraphy. Methods: Cross-sectional study of 69 nursing home patients, 68% women, mean age 83.5 (SD 7.1). Sleep was assessed with the SDI, completed by nursing home staff, and with actigraphy (Actiwatch II, Philips Respironics). The SDI evaluates the frequency, severity, and distress of seven sleep-related behaviors. Internal consistency of the SDI was evaluated by Cronbach’s alpha. Spearman correlations were used to evaluate the convergent validity between actigraphy and the SDI. Test performance was assessed by calculating the sensitivity, specificity, and predictive values, and by ROC curve analyses. The Youden’s Index was used to determine the most appropriate cut-off against objectively measured sleep disturbance defined as <6h nocturnal total sleep time (TST) during 8h nocturnal bed rest (corresponding to SE<75%). Results: The SDI had high internal consistency and convergent validity. Three SDI summary scores correlated moderately and significantly with actigraphically measured TST and wake-after-sleep-onset. A cut-off score of five or more on the SDI summed product score (sum of the products of the frequency and severity of each item) yielded the best sensitivity, specificity, predictive values, and Youden’s Index. Conclusion: We suggest a clinical cut-off for the presence of disturbed sleep in institutionalized dementia patients to be a SDI summed product score of five or more. The results suggest that the SDI can be clinically useful for the identification of disrupted sleep when administered by daytime staff in a nursing home context. ClinicalTrials.gov Identifier: NCT03357328